A Systematic Review and Meta-Analysis of Front-line Anthracycline-Based Chemotherapy Regimens for Peripheral T-Cell Lymphoma. (16th June 2011) - AbouYabis AbouYabis, Abeer N. Abeer N.; Shenoy Shenoy, Pareen J. Pareen J.; Sinha Sinha, Rajni Rajni; Flowers Flowers, Christopher R. Christopher R.; Lechowicz Lechowicz, Mary Jo Mary Jo
Abstract : Anthracycline-based chemotherapy remains standard treatment for peripheral T-cell lymphoma (PTCL) although its benefits have been questioned. We performed systematic literature review and meta-analyses examining the complete response (CR) and overall survival (OS) rates for patients with PTCL. The CR rate for PTCL patients ranged from 35.9% (95% CI 23.4–50.7%) for enteropathy-type T-cell lymphoma (ETTL) to 65.8% (95% CI 54.0–75.9%) for anaplastic large cell lymphoma (ALCL). The 5-year OS was 38.5% (95% CI 35.5–41.6%) for all PTCL patients and ranged from 20.3% (95% CI 12.5–31.2%) for ETTL to 56.5% (95% CI 42.8–69.2%) for ALCL. These data suggest that there is marked heterogeneity across PTCL subtypes in the benefits of anthracycline-based chemotherapy. While anthracyclines produce CR in half of PTCL patients, this yields reasonable 5-year OS for patients with ALCL but not for those with PTCL-NOS or ETTL. Novel agents and regimens are needed to improve outcomes for these patients.